Assessment of milk extracellular vesicle (EV) in vitro bioactivity - Oliver, Charlotte Amélie Caroline (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2024)
Extracellular Vesicles (EVs) are small particles involved in cell-to-cell communication. They have been identified in numerous biological fluids, including milk. Milk EVs serve to communicate between mother and infant, potentially conferring health benefits. Whether next-generation infant milk formula should be enriched with bovine milk EVs is a hot research topic. The first objective of this project was to evaluate the fate of bovine milk EVs during the gut transit of milk in the human infant. A static in vitro gastrointestinal digestion (GI), adapted for the infant's gut, was performed on bovine milk. Following GI digestion, EVs were collected and analysed using SDS-PAGE, immunoblotting, nanoparticle tracking analysis and atomic force microscopy. Bovine milk EVs survived gastric digestion. However, reductions in signal intensities of EV marker, tumour susceptibility gene 101, xanthine dehydrogenase and cluster of differentiation 9 (CD9) indicated that EVs were disrupted during the intestinal phase. This was not due to bile concentration but primarily due to digestive enzymes. EVs concentration was also lower post GI digestion, compared to EVs concentration in undigested milk. Nonetheless, at the end of the intestinal phase, EVs were observed using atomic force microscopy, demonstrating that a portion remains intact. The second aim of this thesis was to investigate how milk EVs and individual components of EVs can modulate gut barrier integrity and permeability using in vitro models. Polarised enterocytes (i.e., Caco-2 monolayers) were treated with EVs or major EV components (phospholipids; sphingomyelin, phosphatidylethanolamine and proteins; xanthine oxidase and CD9). Monolayer’s health was monitored by measuring barrier integrity, paracellular permeability and inflammatory status. Moreover, an in vitro model of a newborn gut barrier was employed to assess the ability of milk EVs to promote barrier maturity for this life stage. Intact milk EVs increased the concentration of tight junction proteins, Claudin-1 and Occludin, but did not affect integrity or permeability in Caco-2 monolayers. In the infant gut model, transepithelial electrical resistance levels were significantly increased in monolayers treated with EVs compared to controls. EV components (CD9, xanthine oxidase and sphingomyelin) increased tight junction protein Junctional Adhesion Molecule 1 in Caco-2 monolayers compared to controls. Furthermore, CD9 significantly increased transepithelial electrical resistance values. These findings show that EVs and EV cargo can improve the maturation and integrity of the intestinal barrier. The function of bioavailable EVs and EV components on downstream target cells is unknown. Infancy is a period of rapid growth routinely measured in body weight. Muscles are a major contributor to lean body mass and adipose tissue is responsible for fat mass. Thus, the final objective of this thesis was to study the biological activity of milk EVs, bioavailable EVs, or bioavailable EV components on adipocytes and muscle cells. Bioavailable samples were collected from basolateral chambers of Caco-2 monolayers treated with EVs or EV components. EVs significantly increased the mammalian target of rapamycin protein phosphorylation and concentration of the transcription factor myogenin in C2C12 myotubes compared to media controls. EVs also inhibited 3T3-L1 adipocyte differentiation and increased glycerol release compared to controls. Basolateral EVs sample enhanced ribosomal protein S6 kinase beta-1phosphorylation in C2C12 myotubes compared with basolateral control. These results demonstrate that if bioavailable EVs can influence muscle protein synthesis and muscle cell differentiation which, in turn, may modulate growth trajectories. In conclusion, bovine milk EVs (a) do not survive the upper gut unscathed, (b) do promote gut barrier health, and (c), if bioavailable, can modulate muscle metabolic function. This thesis provides in vitro evidence of a potential positive health benefit for infants from the consumption of bovine EVs.
APPROVED
Keywords: digestion; gut barrier; myotubes; adipocytes; enterocytes; extracellular vesicles; infant milk formula; milk